Uterine Incarceration and Acute Urinary Retention: An Overlooked Diagnosis - Omar A. Baghlaf, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Incarceration of a gravid uterus is a rare cause of urinary retention in pregnancy; with only 22 cases reported in the literature since 1877. Reported is a case of a 24 year old primigravida presented at King Abdulaziz University Hospital, Jeddah, Saudi Arabia; with her second attack of acute urinary retention at 14 weeks of gestation over a 24 hour period. Successful reduction of her incarcerated uterus was achieved manually. It was carried out in the emergency room by a senior obstetrician with minimal discomfort and no complications. The rest of her pregnancy was uneventful and throughout, she had no further recurrence. She had an uncomplicated vaginal delivery at term. Unexplained recurrent urine retention in pregnancy should draw the attention to uterine incarceration. Awareness to the emergency room staff and obstetricians is primal for early diagnoses. Early correction is considered easier and prevents potential serious maternal and fetal complications. In addition, it permits the patient to have a chance of a vaginal delivery. There is no standard protocol for the management of these cases, and information is based on literature review and case reports, therefore; reporting is encouraged